2014
DOI: 10.1111/cge.12443
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hematological parameters in α‐thalassemia individuals co‐inherited with erythroid Krüppel‐like factor mutations

Abstract: Phenotypic variations in α-thalassemia mainly depend on the defective α-globin gene number. Genetic modifiers of the phenotype of Hemoglobin H (HbH) disease were poorly reported, apart from β-thalassemia allele that was identified ameliorating the severity of α-thalassemia. Because erythroid Krüppel-like factor (KLF1) mutations can modulate the red blood phenotype, we evaluated its effect on the α-thalassemia phenotype. Overall, we identified 72 subjects with five different KLF1 heterozygous mutations in 1468 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
2
19
0
1
Order By: Relevance
“…The KLF1 gene has been associated with various phenotypes, both in humans and mice, including hereditary persistence of fetal hemoglobin [19,29,30,31,32,33,34,35]. Recent studies have demonstrated that the KLF1 zinc finger protein regulates the final switch from fetal to adult globin expression using two pathways: directly, it preferentially binds to the promoter element CACCC of the β-gene acting as a switching factor, and indirectly, it binds to a second transcription factor, BCL11A, which in turn plays the role of a repressor of γ-globin expression [31,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…The KLF1 gene has been associated with various phenotypes, both in humans and mice, including hereditary persistence of fetal hemoglobin [19,29,30,31,32,33,34,35]. Recent studies have demonstrated that the KLF1 zinc finger protein regulates the final switch from fetal to adult globin expression using two pathways: directly, it preferentially binds to the promoter element CACCC of the β-gene acting as a switching factor, and indirectly, it binds to a second transcription factor, BCL11A, which in turn plays the role of a repressor of γ-globin expression [31,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…55 There is a mild but statistically significant decrease in mean cell volume in the presence of a class 2 or 3 KLF1 variant, but this is not noticeable in routine diagnostics ( Figure 3). 55 KLF1 directly activates the HBB gene, 11,12,45 and partial correction of the a-globin:b-globin chain ratios would be expected to ameliorate disease severity.…”
Section: Prevalence Of Klf1 Variants and Interactions With Hemoglobinmentioning
confidence: 95%
“…In Southern China, the combined incidence of class 2 and 3 KLF1 variants (1.3%) is remarkably high, whereas in Northern China it is low, which correlates with the distribution of hemoglobinopathies in these regions. Consequently, co-inheritance of hemoglobinopathies and KLF1 variants is common 7,55 and is likely to be the case in other areas where hemoglobinopathies are endemic such as the Mediterranean 8,47 and Southeast Asia. 4,[55][56][57] The incidence of KLF1 mutations in Africa has not been tested, although there are reports of KLF1 variants in patients of African descent.…”
Section: Prevalence Of Klf1 Variants and Interactions With Hemoglobinmentioning
confidence: 99%
See 1 more Smart Citation
“…Only with the combination of two defective alleles do the patients exhibit symptoms, allowing the mutations to be passed with no harm to the carrier. In fact, there are suggestions that some mutations in KLF1 can ameliorate the symptoms of diseases such as haemoglobinopathies as they are more common in thalassemia endemic regions (Liu et al, 2014a, Yu et al, 2014 and can result in high expression of foetal haemoglobins.…”
Section: Klf1 and Diseasementioning
confidence: 99%